The Role of Distance from Home to Hospital on Parental Experience in the NICU: A Qualitative Study - Stephanie L. Bourque; Venice N. Williams; Jessica Scott; Sunah S. Hwang (MDPI AG, 2023)
Prolonged admission to the neonatal intensive care unit presents challenges for families, especially those displaced far from home. Understanding specific barriers to parental engagement in the NICU is key to addressing these challenges with hospital-based interventions. The objective of this qualitative study was to explore the impact of distance from home to hospital on the engagement of parents of very preterm infants (VPT) in the neonatal intensive care unit (NICU). We used a grounded theory approach and conducted 13 qualitative interviews with parents of VPT who were admitted ≥14 days and resided ≥50 miles away using a semi-structured interview guide informed by the socio-ecological framework. We used constant comparative method with double coders for theme emergence. Our results highlight a multitude of facilitators and barriers to engagement. Facilitators included: (1) individual-delivery preparedness and social support; (2) environmental-medical team relationships; and (3) societal-access to perinatal care. Barriers included: (1) individual-transfer stressors, medical needs, mental health, and dependents; (2) environmental-NICU space, communication, and lack of technology; and (3) societal-lack of paid leave. NICU parents with geographic separation from home experienced a multitude of barriers to engagement, many of which could be addressed by hospital-based interventions.